2016
DOI: 10.3389/fpsyg.2016.01550
|View full text |Cite|
|
Sign up to set email alerts
|

“To be or not to be Retained … That’s the Question!” Retention, Self-esteem, Self-concept, Achievement Goals, and Grades

Abstract: Keeping students back in the same grade -retention -has always been a controversial issue in Education, with some defending it as a beneficial remedial practice and others arguing against its detrimental effects. This paper undertakes an analysis of this issue, focusing on the differences in student motivation and self-related variables according to their retention related status, and the interrelationship between retention and these variables. The participants were 695 students selected from two cohorts (5th … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 70 publications
4
43
0
2
Order By: Relevance
“…Students who feel connected to the school would be more engaged in their studies with, consequently, better academic performance (Blum, 2005). On the other hand, we found that having repeated a school grade was inversely correlated to academic performance, which corroborates with the results of Peixoto et al (2016), in which students who have repeated a school grade showed lower achievement and lower self-esteem and academic self-concept. Likewise, in the present study, having repeated a school grade was inversely correlated with behavioral adjustment self-concept and intellectual self-concept for boys, and inversely correlated with intellectual self-concept for girls (data not shown).…”
Section: Discussionsupporting
confidence: 90%
“…Students who feel connected to the school would be more engaged in their studies with, consequently, better academic performance (Blum, 2005). On the other hand, we found that having repeated a school grade was inversely correlated to academic performance, which corroborates with the results of Peixoto et al (2016), in which students who have repeated a school grade showed lower achievement and lower self-esteem and academic self-concept. Likewise, in the present study, having repeated a school grade was inversely correlated with behavioral adjustment self-concept and intellectual self-concept for boys, and inversely correlated with intellectual self-concept for girls (data not shown).…”
Section: Discussionsupporting
confidence: 90%
“…In turn, they do not exhibit performance-or avoidance-focused tendencies. A group of students holding a dominant tendency toward learning is identified in the vast majority of goal profile studies, both in relation to mathematics (e.g., Turner et al, 1998;Berger, 2012;Schwinger and Wild, 2012;Schwinger et al, 2016) and studying in general (Kolić-Vehovec et al, 2008;Tapola and Niemivirta, 2008;Pulkka and Niemivirta, 2013;Peixoto et al, 2016;Zhang et al, 2016). Given that the main schoolwork focus for these students is on learning, understanding, improvement, and self-comparison, their motivational profile appears very favorable.…”
Section: Achievement Goal Orientation Profiles: More Cross-domain Genmentioning
confidence: 99%
“…In turn, students who exhibit low goal profiles have shown to manifest clearly less functional profile with regard to academic and socio-emotional functioning; for example, low performance, low enjoyment, high anxiety, and high boredom in mathematics ( Conley, 2012 ; Jang and Liu, 2012 ). Finally, students mainly emphasizing work-avoidance orientation have shown to exhibit the most unfavorable outcomes, for instance, depressive symptoms, cynicism, low engagement and valuing of school, relatively poor achievement, and grade retention ( Kolić-Vehovec et al, 2008 ; Tuominen-Soini et al, 2008 , 2012 ; Peixoto et al, 2016 ) and, in mathematics, low individual interest, utility value, and perceived ability and high anxiety ( Berger, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is debate both nationally as in the international literature on the usefulness of having to repeat a class. 42 43 In the context of long periods of missed time at school, getting more time may actually be considered beneficial by many children and their parents, in particular, as more than a third of the parents we surveyed reported their child with IBD to lag behind other children of similar age with respect to their physical development. Problems of self-esteem and social interaction deriving from delayed growth and puberty have been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%